Coordination of Architectural Concepts and Construction Systems - Eddy Hermanto (Bandar Lampung University (UBL), 2013)
This paper reported the implementation of coordination between architectural concept and construction system in the area of dr.Kariadi hospital, in Semarang central Java. In principle, the coordination in the design-construction process can achieve the benefits of development by improving the quality of technical design. The use of Tartan Grid concept closely related to the coordination module that integrates seamlessly blend with the application of the concept of green architecture and design quality indicator (dqi) in architectural design can improve the quality of technical design. Furthermore, the construction phase was green construction methods will improve the performance of related construction projects of sustainable keyword: minimizing waste and pollutants, and achieved self sufficient. Matters are very useful for the future utilization of the building through post-occupancy evaluation.